Nanotechnology‐based drug delivery treatments and specific targeting therapy for age‐related macular degeneration. Issue 11 (November 2015) - Lin, Tai‐Chi; Hung, Kuo‐Hsuan; Peng, Chi‐Hsien; Liu, Jorn‐Hon; Woung, Lin‐Chung; Tsai, Ching‐Yao; Chen, Shih‐Jen; Chen, Yan‐Ting; Hsu, Chih‐Chien
Abstract : Abstract : Nanoparticles combined with cells, drugs, and specially designed genes provide improved therapeutic efficacy in studies and clinical setting, demonstrating a new era of treatment strategy, especially in retinal diseases. Nanotechnology‐based drugs can provide an essential platform for sustaining, releasing and a specific targeting design to treat retinal diseases. Poly‐lactic‐co‐glycolic acid is the most widely used biocompatible and biodegradable polymer approved by the Food and Drug Administration. Many studies have attempted to develop special devices for delivering small‐molecule drugs, proteins, and other macromolecules consistently and slowly. In this article, we first review current progress in the treatment of age‐related macular degeneration. Then, we discuss the function of vascular endothelial growth factor (VEGF) and the pharmacological effects of anti‐VEGF‐A antibodies and soluble or modified VEGF receptors. Lastly, we summarize the combination of antiangiogenic therapy and nanomedicines, and review current potential targeting therapy in age‐related macular degeneration.